2007
DOI: 10.1016/j.jvs.2006.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after celiac artery coverage during endovascular thoracic aortic aneurysm repair: Preliminary results

Abstract: This limited series supports the suitability, in selected patients, of covering the celiac artery origin for a distal landing zone when the distal sealing zone proximal to the celiac artery is inadequate. We recommend the angiographic evaluation of the collateral circulation between the celiac and superior mesenteric arteries when covering the celiac artery origin is being considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 19 publications
3
47
0
Order By: Relevance
“…Vaddineni et al found that the additional sealing distance gained by covering celiac origin varied within the range of 9-25 mm (5). Similar values are reported in anatomical studies.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Vaddineni et al found that the additional sealing distance gained by covering celiac origin varied within the range of 9-25 mm (5). Similar values are reported in anatomical studies.…”
Section: Discussionsupporting
confidence: 59%
“…Vaddineni et al and belenky et al reported on seven patients each without complications and with good clinical outcome (5,12). Waldenberger et al published a series of 10 patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…The celiac artery and SMA have several collateral pathways. The most commonly noted collateral vessels are the pancreaticoduodenal arcades and the dorsal pancreatic artery (8). The dorsal pancreatic artery is usually the first large side branch of the splenic artery, but it may originate on the celiac artery, the common hepatic artery, or the SMA (8 -11).…”
Section: Discussionmentioning
confidence: 99%
“…Coil embolization of the celiac artery simultaneously with revascularization by bypass grafting has also been reported before stent-graft procedures for TAAA (14). In selected cases of TAAA with an adequate distal landing zone at the level and distal to the celiac artery, the origin of the celiac artery can even be covered safely with a stent-graft if there is good collateral circulation between the SMA and celiac artery (8). Open reconversion to treat type II endoleaks is rarely indicated (5).…”
Section: Discussionmentioning
confidence: 99%
“…14 Vaddineni et al reported seven cases of planned celiac coverage with a thoracic EVAR to secure an adequate distal sealing zone. 15 Six out of the seven cases demonstrated collateral circulation through the gastroduodenal artery between the CA and the SMA before deployment of the stent-graft. There were no deaths, no ischemic abdominal complications, and no type II endoleaks.…”
Section: Discussionmentioning
confidence: 89%